The historical accentuation of masculine nouns in Čakavian and Štokavian Dalmatian dialects in light of Deanović’s Lingvistički atlas Mediterana ﻿ - Schallert, Joseph (Slavia Centralis, 2020)
Mirko Deanović’s Lingvistički atlas Mediterana project led to the publication of a series of articles (1958–1967) devoted to the lexicon of a range of BCS dialects extending along the Dalmatian coast and offshore islands from Čakavian Krk in the north to Old Štokavian Boka Kotorska in the south. Since the data were gathered with due attention to prosodic details, Deanović’s material can be utilized for the purposes of the present paper, which provides a comparative historical analysis of the accentuation of monosyllabic masculine stems attested in Deanović’s corpus. The results of this analysis shed new light on the lexical and geographical domain of “accent type D” in BCS, a topic which has been the focus of scholarly discussion devoted to the evidence for and against Common Slavic “accent paradigm (d)”.